2018
DOI: 10.1002/eat.22880
|View full text |Cite
|
Sign up to set email alerts
|

The moderating role of self‐compassion on weight and shape concerns and eating pathology: A longitudinal study

Abstract: Our findings suggest that high self-compassion may reduce the likelihood that undergraduate students with weight/shape concerns will engage in disordered eating behavior in the first year of college. They also highlight the influence of self-compassion on general stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…Recent studies have also suggested that self-compassion can: buffer against risk factors for eating and body concerns (e.g., Ferreira, Matos, Duarte & Pinto-Gouvei, 2014;Stutts & Blomquist, 2018); prevent the initial occurrence of risk factors (e.g., Ferreira, Pinto, & Duarte, 2013;Marta-Simões, Ferreira, & Mendes, 2016); and reduce existing eating and body image problems (e.g., Breines, Toole, Tu & Chen, 2014;Kelly & Carter, 2015).…”
Section: Is Self-compassion Relevant To the Pathology And Treatment O...mentioning
confidence: 99%
“…Recent studies have also suggested that self-compassion can: buffer against risk factors for eating and body concerns (e.g., Ferreira, Matos, Duarte & Pinto-Gouvei, 2014;Stutts & Blomquist, 2018); prevent the initial occurrence of risk factors (e.g., Ferreira, Pinto, & Duarte, 2013;Marta-Simões, Ferreira, & Mendes, 2016); and reduce existing eating and body image problems (e.g., Breines, Toole, Tu & Chen, 2014;Kelly & Carter, 2015).…”
Section: Is Self-compassion Relevant To the Pathology And Treatment O...mentioning
confidence: 99%
“…Although the adult literature demonstrates that self‐compassion is a malleable construct that has robust associations with health outcomes, only a handful of studies have explored the longitudinal role of self‐compassion in body satisfaction and eating pathology (e.g., Stutts & Blomquist, ). Notably, few studies have investigated the relationship between self‐compassion and body image in adolescents (Mosewich, Kowalski, Sabiston, Sedgwick, & Tracy, ; Rodgers et al, , ), and not one study to date has examined the link between self‐compassion and disordered eating in youth.…”
Section: Introductionmentioning
confidence: 99%
“…Moderator research has shed some light on the factors that accentuate the relationship between BD and EP. For example among women, perfectionism, body surveillance, low self-compassion, neuroticism, low well-being; anxiety, depression, low self-esteem, and having a family member or friend with an ED, have each been found to moderate the relationship between BD and EP (Twamley and Davis, 1999; Tylka, 2004; Downey and Chang, 2007; Brannan and Petrie, 2011; Juarascio et al, 2011; Stutts and Blomquist, 2018). However, to our knowledge, no research has specifically looked at the characteristics of those with low levels of EP relative to their BD.…”
Section: Introductionmentioning
confidence: 99%